Toward a Petri Net Based Model to Control Conflicts of Autonomy between Cyber-Physical & Human-Systems. Issue 32 (2016) - Vanderhaegen, F.
Abstract: A dissonance is a conflict between individual, collective or organizational knowledge. This concept is extended to a conflict of autonomy between components of a human-machine system, such as Cyber-Physical & Human Systems (CPHS). The autonomy of the CPHS is modeled by a triplet representing three sets of knowledge: the Competence, the Availability and the Prescription. The so-called Competence-Availability-Prescription (CAP) model is then proposed to represent the capability of the CPHS to act alone and to control possible emergent behaviours such as conflicts of autonomy in terms of competence, availability and/or prescription. The formalism of the Petri nets is used to model the three CAP model parameters and to control possible conflicts between them. A feasibility study of the application of such CAP model and Petri nets is presented for the car driving domain involving the car driver interacting with Cyber-Physical Systems (CPS) such as an Automated Speed Control System (ASCS).